PENGARUH BIOCHAR TEMPURUNG KELAPA DAN NPKMg 15:15:6:4 TERHADAP PERTUMBUHAN BIBIT TANAMAN PINANG HIBRIDA (Areca catechu L.) PADA MEDIA TANAM PODSOLIK MERAH KUNING - Vicki Sardo L; Sri Mulyani (DINAMIKA PERTANIAN, 2025)
Research has been carried out to determine the interaction effect between coconut shell biochar and NPKMg 15:15:6:4 on the growth of hybrid areca nut (Areca catechu L.) seedlings in yellow-red podzolic planting media. The research was conducted at the experimental farm of the Faculty of Agriculture, Riau Islamic University, Air Dingin Street, Air Dingin Village, Bukit Raya District, Pekanbaru City, for four months from March to July 2024. The research used a completely randomised factorial design consisting of two factors. The first factor was coconut shell biochar, with four treatment levels (0, 75, 150, 225 g per polybag), while the second factor was NPKMg 15:15:6:4, with four treatment levels (0, 2, 4, 6 g per polybag). The parameters observed were plant height, number of leaf midribs, stem diameter, total leaf area, and root volume. Data were analysed statistically and continued at the 5% level of the BNJ test. The results showed that the interaction of coconut shell biochar and NPKMg 15:15:6:4 affected all observation parameters. The best treatment was found at a dose of 225 g coconut shell biochar per polybag and NPKMg 15:15:6:4 6 g per polybag. The main factor of coconut shell biochar influenced all observation parameters. The best treatment was found at a dose of 225 g of coconut shell biochar per polybag. The main factor NPKMg 15:15:6:4 influenced all observation parameters. The best treatment was found at a dose of NPKMg 15:15:6:4 6 g per polybag.